2018
DOI: 10.3390/genes9100469
|View full text |Cite
|
Sign up to set email alerts
|

Viral Biomarkers in Chronic HBeAg Negative HBV Infection

Abstract: Viral biomarkers are important tools for monitoring chronic hepatitis B virus (HBV) hepatitis B early antigen (HBeAg) negative infection, both in its natural course as well as during and after treatment. The biomarkers consist of antibodies against viral epitopes, viral proteins, and molecular surrogate markers of the quantity and transcriptional activity of the stable episomal HBV covalently closed circular DNA (cccDNA) which is located in the nuclei of the infected hepatocytes. HBV deoxyribonucleic acid (DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 136 publications
(154 reference statements)
0
38
0
2
Order By: Relevance
“…Sustained off‐treatment viral suppression is a well‐accepted clinical end‐point of antiviral therapy in patients with CHB. At present, baseline parameters have not been fully established to predict positive or negative outcomes in patients with HBeAg‐negative CHB treated with PEG‐IFN . In this report, our cohort with longitudinal follow‐up demonstrated that low baseline HBV RNA level was associated with response to PEG‐IFN‐based therapy.…”
Section: Discussionmentioning
confidence: 61%
“…Sustained off‐treatment viral suppression is a well‐accepted clinical end‐point of antiviral therapy in patients with CHB. At present, baseline parameters have not been fully established to predict positive or negative outcomes in patients with HBeAg‐negative CHB treated with PEG‐IFN . In this report, our cohort with longitudinal follow‐up demonstrated that low baseline HBV RNA level was associated with response to PEG‐IFN‐based therapy.…”
Section: Discussionmentioning
confidence: 61%
“…31 All three proteins share an identical 149 amino acid sequence. 31,32 HBcAg, p22cr, and HBeAg can all be measured as HBcrAg by serological testing. 33,34…”
Section: Components Of Hbcrag (Fig 2)mentioning
confidence: 99%
“…p22cr is a 22-kDa precore protein present in HBV DNA-negative empty Dane-like particles [ 31 ]. All three proteins share an identical 149 amino acid sequence [ 31 , 32 ]. HBcAg, p22cr, and HBeAg can all be measured as HBcrAg by serological testing [ 33 , 34 ].…”
Section: Surrogate Marker Of Intrahepatic Hbv Replication: Hbcragmentioning
confidence: 99%
“…The HBV surface protein is a very sensitive biomarker for viral infection, given that it is expressed at high levels in all viral infection phases [ 16 ]. In addition to its location in the viral envelope, the surface protein is secreted outside cells through vesicle-mediated exocytosis to form filamentous and spherical SVPs that lack a genome-containing capsid; therefore, the HBV surface protein is a relatively stable biomarker indicating an infection history [ 17 ].…”
Section: Hbv Surface Proteinsmentioning
confidence: 99%